2006
DOI: 10.1002/masy.200690044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Very Small Polymer Particles by Catalytic Polymerization in Aqueous Systems

Abstract: Summary:The preparation of aqueous dispersions of very small particles (size < 30 nm) of various polymers (polyethylenes, stereoregular 1,2-polybutadiene, and polyalkenamers) by catalytic polymerization with a water-soluble catalyst, or with microemulsions of lipophilic catalysts is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…[10] This results in particles without supported process, and their size might be decreased to the nanometer region. [11,12] A major drawback is that only a few catalyst systems tolerate water, the majority being extremely water sensitive. Metallocenes, being able to produce high molecular weight polyolefins, are easily decomposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] This results in particles without supported process, and their size might be decreased to the nanometer region. [11,12] A major drawback is that only a few catalyst systems tolerate water, the majority being extremely water sensitive. Metallocenes, being able to produce high molecular weight polyolefins, are easily decomposed.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, polyolefins produced inside an emulsion have had, thus far, relatively low molecular weights in comparison to metallocene or postmetallocene-catalyzed processes. [11,12] Herein, the utilization of a nonaqueous, oil-in-oil emulsion is proposed as one possibility to overcome these challenges. It has already been shown that water-free emulsions of acetonitrile/hydrocarbon offer the opportunity to use water-sensitive catalytic systems to form polyacetylene.…”
Section: Introductionmentioning
confidence: 99%
“…So as to get rid of this issue, we later proposed to use directly the commercial hydrophobic shape of GC1 using a new alternative [19] inspired by the work of Mecking and coworkers on microemulsion ROMP. [20,21] The approach is based on the use of two aqueous microemulsions: the first one has a dispersed phase composed of the monomers (NB, MMA and Ethyl 2-chloropropionate or I1) whereas the droplets of the second one contain GC1 solubilised in toluene. Once they have been mixed together, thermodynamically driven exchanges between the droplets of both microemulsions enable GC1 to meet the other reagents and thus to trigger off the ROMP of NB and the ATRP of MMA.…”
Section: Second Route: Simultaneous Romp and Atrp From Two Distinct Mmentioning
confidence: 99%
“…24 The stabilisation of oil/water interfaces with surfactants has also potential for structuring of polymer-derived ceramics. The emulsion droplets can be used as templates/microreactors for polymerisation reactions 25,26 and colloid synthesis, 27 which govern the final particle size. Depending on the particle size (crude) turbid unstable emulsions (few microns) and thermodynamically stable translucent microemulsions (10-40 nm) are discerned.…”
Section: Introductionmentioning
confidence: 99%